Fundamental studies of selected Alexandrium spp. at different growth phases and their effects on proteomics of mussels - Hamdan, Nurul Ashima; Mamat, Siti Norhasmiza; Abu Hassan, Muhamad Shafiq; Mohammad Noor, Normawaty; Muhamad Bunnori, Noraslinda (2015)
The naturally occurring phenomenon of dinoflagellates blooming at the water surface brought detrimental effects to the economy as well as the environmental health of the ecosystem affected. Researchers worldwide have been working on finding the feasible solutions towards identifying the causative species as well as inducing factors that favor the outgrowth of that species. Most cases of HABs reported in Malaysia waters are dominated by genus of Alexandrium with some of the species were reported to cause shellfish poisoning. Seasonal monsoon, anthropogenic pollution and ballast water are important elements in stimulating the blooming event. These factors may vary according to places as some species adapt well to extreme conditions while others may elevate under temperate circumstances. In this study, four Alexandrium spp. with various toxicity levels were analyzed using proteomic approaches whereby the protein expressed will determine the precursors responsible for their toxicity properties. The study on the biomolecular part of the microorganisms is vital in order to understand the synthesizing pathway of toxin biomarkers that are unique to the species of interest. The level of protein expressions are compared at different growth stages in which exponential phase will execute high expression of targeted spots when analyzed using 2D electrophoresis technique. This is corresponding to the life cycle of the toxic dinoflagellates where toxins were released upon reaching late exponential phase. Further investigation on the toxicity properties of selected Alexandrium spp. is studied on mussels where the shellfish are fed with toxic Alexandrium tamiyavanichii and non-toxic Alexandrium leei separatedly. Accumulation of toxins was expected as mussels are one type of filter feeders hence the protein expressed will be correlated with the 2D analysis results of previously selected Alexandrium spp